The Influence of 8-Week Aerobic Exercise on Antioxidant Enzym on Young Men - Yunus, Moch. (Interdisciplinary Social Studies, 2023)
Background: Aerobic exercise is indicated to be able to trigger an increase in antioxidant enzyme activity in the human body, which is one indicator of an increase in antioxidant enzyme activity marked by an increase in blood plasma Superoxide dismutase (SOD). Aim: This study aims to examine and analyze the magnitude of the increase in SOD due to aerobic exercise for 8 weeks. Methods: This research is a quasi-experimental research with a quantitative approach and a one group pretest and posttest design. The population in this study were students of the Department of Sports Coaching, State University of Malang, aged 19-20 years, with a normal Body Mass Index (BMI). The sampling technique used purposive sampling, with a total sample of 20 students. Data was collected by measuring blood plasma SOD activity as an indicator of antioxidant enzyme. SOD measurements were carried out before and after the aerobic exercise treatment. Aerobic exercise is carried out with a frequency of 3 times per week, with moderate intensity, for 8 weeks. Data Analysis using t-test in pairs (? = 0.05). Findings: The results showed that the mean and standard deviation of the SOD pretest were 22.68 ± 2.62 U/ml and posttest 29.05 ± 1.44 U/ml, there is an average increase in SOD activity plasma by 21.9% (p=0.021 <0.05).